Cascade charge transfer enabled by incorporating edge-enriched graphene nanoribbons for mesostructured perovskite solar cells with enhanced performance. (October 2018) - Meng, Xiangtong; Cui, Xun; Rager, Matthew; Zhang, Shuguang; Wang, Zewei; Yu, Jiwoo; Harn, Yeu Wei; Kang, Zhitao; Wagner, Brent K.; Liu, Yang; Yu, Chang; Qiu, Jieshan; et al.
Abstract: The ability to facilitate charge transfer in electron transport layer (ETL) is highly desirable for high-efficiency perovskite solar cells (PSCs). Herein, we report the judicious design of ETL composed of edge-enriched graphene nanoribbons (GNRs) and TiO2 nanocrystals to enable markedly improved charge carrier conductivity and, more importantly, well-aligned energy levels at the perovskite/ETL/fluorine doped tin oxide (FTO) interfaces for imparting the cascade charge transfer, thereby leading to improved power conversion efficiency (PCE) of PSCs. The investigation into the influence of the GNR content within ETL on device performance demonstrated that excessive GNRs are detrimental for charge transfer as they block the contact between TiO2 and perovskite. In contrast to devices using pure TiO2 as ETL with a PCE of 15.87%, the PSCs employing GNRs-incorporated ETL display the improved photovoltaic performance with a highest PCE of 17.69%, a steady-state efficiency output of 17.05%, and a reduced current-voltage hysteresis. Subsequently, a systematic photo-carrier dynamics study revealed that the performance enhancement was a direct consequence of (a) the promoted fill factor and open circuit voltage due to the improved electron diffusion coefficient and the longer charge recombination time, (b) the increased charge collection efficiency owing to the cascade charge transfer from TiO2 to GNRs to FTO electrode, resulting in a higher external quantum efficiency and thus a larger short circuit current density and (c) the suppressed current-voltage hysteresis ascribed to the increased charge transfer noted above. Finally, a markedly improved long-term stability was manifested. As such, the rational incorporation of edge-enriched GNRs represents a feasible and robust strategy to formulate promising ETLs for high-efficiency and stable PSCs. Graphical abstract: A robust ETL constructed by incorporating GNRs with rich electrochemically active edges into TiO2 paste for enabling cascade charge transfer when capitalizing on in m-PSCs is first reported. An enhanced PCE of 17.69%, a steady-state efficiency output of 17.05%, and a largely reduced current-voltage hysteresis are achieved, outperforming the device with pure TiO2 ETL. The photo-carrier dynamics are subsequently scrutinized by a combined IMPS and IMVS study. fx1 Highlights: An electron transport layer (ETL) with graphene nanoribbons (GNRs) and TiO2 for m-PSCs is reported. An enhanced PCE of 17.69% and a largely reduced current-voltage hysteresis are achieved. Photo-carrier dynamics are scrutinized by intensity-modulated photocurrent/photovoltage spectroscopy. The loading of GNRs in ETL stands out as a viable and low-cost strategy to effectively transfer charges.